Who counts? Demography of swidden cultivators in southeast asia - Ole Mertz (2018)
Swidden cultivators are often found as a distinct category of farmers in the literature, but rarely appear in population censuses or other national and regional classifications. This has led to a worldwide confusion on how many people are dependent on this form of agriculture. The most often cited number of 200-300 million dates back to the early 1970s, but the source is obscure. We assess available, published data from nine countries in Southeast Asia and conclude that on this basis it is not possible to provide a firm estimate of the number of swidden cultivators in the region. A conservative range of 14-34 million people engaged in swidden cultivation in the region is suggested, however. We argue that along with improved knowledge of swidden livelihoods, there is an urgent need to develop techniques that will allow for better estimates of swidden populations in order to secure appropriate rural development and poverty reduction in swidden areas. © Springer Science+Business Media, LLC 2009.